Effect of Biennial Wormwood (Artemisia biennis) Interference on Sunflower Yield and Seed Quality. Issue 1 (March 2016) - Lewis, Derek W.; Cavalieri, Andrea; Gulden, Robert H.
Abstract : Biennial wormwood has been increasing in Manitoba, Canada, but information is limited on the potential of biennial wormwood to reduce crop yields. Field experiments were conducted over 5 site-yr throughout southern Manitoba in 2010 and 2011 to determine the effect of biennial wormwood density and relative time of biennial wormwood seedling recruitment on sunflower growth, development, yield, and seed quality. Biennial wormwood was broadcast on the soil surface at six densities into sunflowers planted in 75-cm rows, either at the same time the sunflower crop was planted (early weed seedling recruitment) or when the sunflowers were at about the four-leaf stage (late weed seedling recruitment). When biennial wormwood emerged at about the same time as the sunflowers, yield was reduced by up to 46%. Early-recruiting biennial wormwood had minimal effect on sunflower growth and development, but sunflower achene size and individual achene weight were reduced, even when no effect on sunflower yield was observed. Biennial wormwood plants that recruited after the four-leaf stage of the sunflower crop had no effect on sunflower yield or seed quality.